CHARGE syndrome: the phenotypic spectrum of mutations in the CHD7 gene. Issue 4 (9th September 2005) - Jongmans, M C J; Admiraal, R J; van der Donk, K P; Vissers, L E L M; Baas, A F; Kapusta, L; van Hagen, J M; Donnai, D; de Ravel, T J; Veltman, J A; Geurts van Kessel, A; De Vries, B B A; et al.
Abstract : Background: CHARGE syndrome is a non-random clustering of congenital anomalies including coloboma, heart defects, choanal atresia, retarded growth and development, genital hypoplasia, ear anomalies, and deafness. A consistent feature in CHARGE syndrome is semicircular canal hypoplasia resulting in vestibular areflexia. Other commonly associated congenital anomalies are facial nerve palsy, cleft lip/palate, and tracheo-oesophageal fistula. Specific behavioural problems, including autistic-like behaviour, have been described. The CHD7 gene on chromosome 8q12.1 was recently discovered as a major gene involved in the aetiology of this syndrome. Methods: The coding regions of CHD7 were screened for mutations in 107 index patients with clinical features suggestive of CHARGE syndrome. Clinical data of the mutation positive patients were sampled to study the phenotypic spectrum of mutations in the CHD7 gene. Results: Mutations were identified in 69 patients. Here we describe the clinical features of 47 of these patients, including two sib pairs. Most mutations were unique and were scattered throughout the gene. All patients but one fulfilled the current diagnostic criteria for CHARGE syndrome. No genotype-phenotype correlations were apparent in this cohort, which is best demonstrated by the differences in clinical presentation in sib pairs with identical mutations. Somatic mosaicism was detected in the unaffected mother of a sib pair, supporting the existence of germline mosaicism. Conclusions: CHD7 mutations account for the majority of the cases with CHARGE syndrome, with a broad clinical variability and without an obvious genotype-phenotype correlation. In one case evidence for germline mosaicism was provided.